Information Technology: Its Impact on Product Competitiveness Mediated by Product Innovation in SMEs - Subandi, Subandi; Lourensius L. Tarigan, Nerys (Lembaga Penelitian Universitas YARSI, 2024)
One of the main challenges for SMEs players is the application of information technology to increase product innovation and competitiveness This study aims to examine a research model that is expected to provide insights into the impact of information technology on product innovation and its influence on product competitiveness. Data were collected from 100 respondents involved in SMEs through a distributed questionnaire. This research conducted three tests on the hypotheses based on indicator variables using SEM-PLS (Partial Least Squares) analysis with SmartPLS software. These tests include the outer model, the inner model, and hypothesis testing. The results of hypothesis testing show a significant positive direct impact of information technology on both product competitiveness and product innovation. Additionally, there is a significant positive direct impact of product innovation on product competitiveness.